Studi Efektivitas Jumlah Data Pengukuran Nilai Potensial Terhadap Kinerja BEIA dalam Mendeteksi Lokasi Korosi Beton Bertulang - ., Israr; ., affandi; Huzni, Syifaul; Fonna, Syarizal; Tanjung, Iqbal (Rekayasa Material, Manufaktur dan Energi, 2024)
Corrosion is a very serious problem. It could not be prevented due to natural events which trigger corrosion itself. Many failures and losses caused by suboptimal early prevention of corrotion, such as the sudden collapse of buildings and infrastructure which incurring loss and casualties. One methode that is widely used to detect corrosion is the Half Cell Potential Mapping methode. However, there is shortage interpretation of data in the methods who need to be considered. Then, the software who could detect early failures caused by corrosion is developing. On of them is Boundary Element Invers Analysis (BEIA). BEIA has succeeded in detecting the location of corrosion in reinforced concrete with 5% error percentage. However, it is necessary to increas its ability. This research aims to find the effect of the amount of potensial value measurement data on BEIA ability to detect corrosion in reinforced concrete. BEIA developed by combining the application of Boundary Element Method (BEM) and Particle Swarm Optimization (PSO). BEM used to calculate potential values on concrete surface, while PSO evaluates the cost function for detecting corrosion in reinforcing steel in concrete. This research wa conducted on reinforced concrete 3-dimensional geometry, namely length, widht and height. In the middle of the concrete there is reinforcement which has corrosion. The parameter of the amount of potential value measurement data was varied in order to get better input in improving the performance of BEIA. That were 5,10, 15 and 20. The simulation showed that the used of the potential value measurement data of 20 had less error percentage value obtained at 650 cm x 50 cm geometry was 0.2 %. These proves that the larger potential value measurement data could improved BEIA performance.